Hubungan Antara Harapan dalam Menghadapi Kecemasan Masa Depan pada Mahasiswa Semester Akhir di Yogyakarta - Luthfiah Kusuma Safitri; Agus Salim (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Future anxiety is an emotional condition characterized by constant worry about the potential occurrence of negative events in the future. This condition is often accompanied by excessive thoughts related to uncertainty and a lack of control over what will happen. Final-year students tend to be vulnerable to future anxiety due to various pressures, such as academic burdens, career planning, and social demands. However, the aspect of hope, as a positive psychological element, can play an important role in helping them cope with these pressures. This study aims to examine the relationship between future anxiety and hope among final-year students in Yogyakarta. A total of 96 respondents, aged 20–25 years, were selected using purposive sampling. The research employed a quantitative approach, and the data were analyzed using Pearson Product Moment correlation through SPSS version 23. The results of the analysis indicate a significant relationship between future anxiety and hope, with a correlation coefficient of r = 0.529 (p = 0.000). These findings suggest that the higher the hope students have, the higher the future anxiety they experience. Conversely, the lower the level of hope, the lower the future anxiety felt by final-year students.